Biodistribution of PLGA and PLGA/chitosan nanoparticles after repeat-dose oral delivery in F344 rats for 7 days. (November 2014) - Navarro, Sara M; Darensbourg, Caleb; Cross, Linda; Stout, Rhett; Coulon, Diana; Astete, Carlos E; Morgan, Timothy; Sabliov, Cristina M
Aim : To quantify in vivo the biodistribution of poly(lactic-co-glycolic) acid (PLGA) and PLGA/chitosan nanoparticles (PLGA/Chi NPs) and assess if the positive charge of chitosan significantly enhances nanoparticle absorption in the GI tract.Material & methods : PLGA and PLGA/Chi NPs covalently linked to tetramethylrhodamine-5-isothiocyanate (TRITC) were orally administered to F344 rats for 7 days, and the biodistribution of fluorescent NPs was analyzed in different organs.Results : The highest amount of particles (% total dose/g) was detected for both treatments in the spleen, followed by intestine and kidney, and then by liver, lung, heart and brain, with no significant difference between PLGA and PLGA/Chi NPs. Conclusion : Only a small percentage of orally delivered NPs was detected in the analyzed organs. The positive charge conferred by chitosan was not sufficient to improve the absorption of the PLGA/Chi NPs over that of PLGA NPs.